2015
DOI: 10.5213/inj.2015.19.3.178
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Continuous Positive Airway Pressure Therapy on Nocturia in Patients With Obstructive Sleep Apnea: A Systematic Review and Meta-Analysis

Abstract: Purpose:To assess the efficacy of the continuous positive airway pressure (CPAP) on nocturia in patients with obstructive sleep apnea (OSA).Methods:A literature review was performed to identify all published clinical trials of CPAP for the treatment of nocturia. The search included the following databases: MEDLINE, Embase, and the Cochrane Controlled Trials Register. The reference lists of the retrieved studies were also investigated.Results:Five publications involving a total of 307 patients were used in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 29 publications
2
35
0
6
Order By: Relevance
“…Nocturia often improves in patients with OSA using continuous positive airway pressure . Patients who undergo uvulopalatopharyngoplasty for their OSA have also seen an improvement in nocturia symptoms …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nocturia often improves in patients with OSA using continuous positive airway pressure . Patients who undergo uvulopalatopharyngoplasty for their OSA have also seen an improvement in nocturia symptoms …”
Section: Resultsmentioning
confidence: 99%
“…40 Nocturnalpolyuriamaybebehavioural(excessfluidintake),druginducedorapartofglobalpolyuria.Systemicdiseasessuchascongestive heart failure,venous stasis in the lower extremities, obstructive sleep apnoea (OSA), renal tubular dysfunction, hepatic failure and hypoalbuminaemiacancausefluidandelectrolytesequestrationand, therefore, may also be reasons for nocturnal polyuria. 31,33,41…”
Section: Nocturnal Polyuriamentioning
confidence: 99%
“…CPAP also seems to be effective in reducing the frequency of nocturia and the associated nighttime polyuria 21 . In a meta‐analysis by Wang et al, 22 it was concluded that CPAP possibly is an effective treatment for reducing nocturia associated with OSAS and improves the QoL in these patients. At this time CPAP is not the only treatment option in OSAS and the effect of other treatment options like lifestyle changes, oral devices, and surgical procedures must also be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are few reports of the change in nocturia frequency after intervention for clinically relevant sleep disturbance, aside from sleep‐disordered breathing (SDB). Following continuous positive airway pressure (CPAP) treatment for SDB a reduction of up to 2.28 nocturia episodes per night has been reported . Of interest, given the high risk for frequent nocturia with urinary urgency, is a recent report of women with moderate or severe SDB who experienced a reduction in overactive bladder symptoms after 3 months of CPAP therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Following continuous positive airway pressure (CPAP) treatment for SDB a reduction of up to 2.28 nocturia episodes per night has been reported. [18][19][20] Of interest, given the high risk for frequent nocturia with urinary urgency, is a recent report of women with moderate or severe SDB who experienced a reduction in overactive bladder symptoms after 3 months of CPAP therapy. 21 Similarly, in a CPAP trial controlled for type 2 diabetes mellitus, 90% of participants across both groups evidenced improved nocturia.…”
Section: Discussionmentioning
confidence: 99%